Pangsa Ekonomi Sektoral dan Tipologi Daerah di Wilayah Jawa Bagian Tengah - Agus Arifin; Dijan Rahajuni (EKO-REGIONAL, 2007)
Economic potency in region of central Java is interesting to analyze. On 2000 to 2004, this region had referred to structural economic changing. Basic sectors, which was being prime sectors on 2000, has declined the role be the main regional income on 2004. The new cities establishment on this region, late of 90’s, may have important role to the structural change. It has driven modern activities that gave significant contribution to regional income. Nevertheless, regional typology shows the income disparities among the regency on this regions. Especially, the regions with low per capita income and coincide with low economic growth should need to concern. Without appropriate and wise policy, these regions will always left behind from the other regions if they are compared by the regions that have better typology.  Keywords: economic potency, regional typology, income disparities